EVALUATION OF CHICKPEA (Cicer arietinum L.) GENOTYPES FOR GENETIC VARIABILITY AND MECHANIZATION POTENTIAL UNDER GANGETIC PLAINS - A. P. Singh; S. Majumdar; G. V. Kumar; W. Emam; Y. Tashkandy; Md. Hedayetullah; H. L. Singh; P. K. Singh; S. Ray; F. Homa; A. Matuka; R. Sadhukhan (Journal of Animal and Plant Sciences, 2025)
Chickpea (Cicer arietinum L.), a vital pulse crop belonging to the Leguminosae family, is crucial for global food security. Urgent mechanization needs arise due to rising production costs and a workforce shift from agriculture. However, the mechanization of chickpea farming lags behind that of cereal crops, hindering its global expansion. India, with an annual production of 9.938 million tonnes, aims to enhance efficiency by developing chickpea varieties suitable for mechanized harvesting. The present study aimed to evaluate 43 chickpea genotypes for mechanical harvesting traits, yield components, and genetic diversity. Variability studies revealed ample variation, with high heritability in traits like first pod height, pods per plant, and seed index, suggesting additive gene action. Positive associations at both phenotypic and genotypic levels indicated the significance of these traits for seed yield improvement. Path analysis emphasized the positive influence of biological yield, harvest index, and first pod height on seed yield per plant. Traits such as first pod height in actual conditions, seed index, days to 50% flowering, and harvest index contributed significantly to genetic divergence. Cluster analysis identified promising genotypes (e.g., ICC 6811, ICC 13816) for hybridization, as they exhibited higher inter-cluster distances. Principal component analysis highlighted six principal components (PCs), with the PC1 and PC2 contributing the 40.7% of total variance. Promising genotypes for mechanical harvesting included ICC 12492, ICC 11627, ICC 440, ICC 2065, and ICC 1164, based on plant growth habit, plant height, first pod height, pods per plant, and seed yield. This study provides essential insights for future hybridization programs as well as trait introgression that make mechanical harvesting feasible.
Keywords: chickpea; mechanized harvesting; genetic diversity; hybridization.